Value preference in forensic population: a systematic literature review of delay discounting among those who have committed an offence - Sebalo, Ivan; Darashkevich, Darya; Kostelníková, Stela; Voldřichová, Johana (Frontiers in Behavioral Neuroscience, 2025)
IntroductionDelayed rewards discounting describes the tendency to choose a smaller immediate rewards instead of a larger delayed rewards. Considering the central role of impulsivity in models accounting for criminal conduct in general and violent behavior, the relationship between delayed rewards discounting and crime is likely to be present. Thereby extending the reported association with the addictive behavior. However, it is unclear whether it should be treated as a risk or an etiological factor. Consequently, the current literature review aims to summarize the existing empirical research focused on this aspect of impulsive decision-making among those who have offended.MethodsThe review was performed in accordance with the 2021 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search of the Web of Science, PubMed, and PsycINFO databases was conducted in February 2025.ResultsThe initial search yielded 1,251 articles. After exclusion of 250 duplicates, 1,001 titles were screened for relevance, leading to 556 abstracts. After reading them, 162 full-text articles were inspected, leaving 25 articles included in the review.ConclusionThis review demonstrates that although delayed rewards discounting is associated with general criminal conduct, the association with violence specifically is tenuous. Furthermore, several studies point out that influencing serotonergic functioning, behavioral modeling, or future representations have the potential to influence it. However, further detailed research is needed.